High-thermal-conductivity wear-resistant material for circulating fluidized bed boiler
By using high-thermal and wear-resistant composite materials in circulating fluidized bed boilers, the problem of material wear in high temperature environments is solved, high wear resistance and good thermal conductivity of the material are achieved, and the service life of the boiler is extended.
Patent Information
- Application Number
- CN202411613013.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing circulating fluidized bed boiler materials are prone to wear in high temperature environments, resulting in a decrease in heat dissipation performance and shortened service life.
Composite materials prepared by mixing highly thermally conductive components and wear-resistant components, including aluminum alloys, silicon nitrides, silicon aluminum nitrides, magnesium-based ceramic composites and cemented carbide coatings, are treated by sintering and coating Reinforced material wear resistance and thermal conductivity.
Without affecting the heat dissipation properties of the boiler, the wear resistance of the material is significantly improved, the service life is extended, and good thermal conductivity is maintained, so that even if wear occurs, it will not affect heat dissipation.
Smart Images

Figure CN119433390A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lining materials for coal-fired power station boilers, in particular to a high heat-conducting and wear-resistant material for circulating fluidized bed boilers. Background Art
[0002] The circulating fluidized bed is a new type of coal-fired boiler. The coal is crushed into pieces less than 10 mm and then passed into the furnace. The coal is fully mixed with the inert high-temperature materials in the furnace through the air distribution at the bottom of the furnace to form a fluidized combustion state. In the subsequent process, a gas-solid separation device is installed to collect the incompletely burned coal particles and continue to burn them. The advantage of the circulating fluidized bed boiler is that the fuel can be fully utilized. Compared with the pulverized coal furnace, it is not necessary to crush the coal fuel with high quality to achieve the purpose of full combustion and utilization of the coal. In addition, the circulating fluidized bed boiler does not require high quality fuel. Poor quality fuel can be fully burned in the boiler. The combustion of the circulating fluidized bed boiler includes two processes: internal and external circulation. The internal circulation is the circulation process in the furnace, that is, the high-speed flue gas in the furnace is in close contact with the solid particles with strong turbulence disturbance carried by it, and there is a fluidized combustion reaction process with a large number of particles back-mixed. The external circulation is the process of collecting most of the high-temperature solid particles outside the furnace and sending them back to the furnace to participate in the combustion again. This special combustion method gives the circulating fluidized bed boiler many characteristics that traditional boilers do not have.
[0003] Although the circulating combustion method improves the combustion efficiency, in the CFB boiler, the fuel and inert material (sand) are continuously circulated under the action of the airflow. These particles rub against the surface of the equipment inside the boiler, causing wear. The airflow velocity of the fluidized bed is relatively high, and the impact force of the particles is enhanced, which increases the wear on the internal parts of the boiler. The existing technologies are all improvements on the high temperature resistance or high thermal conductivity of the circulating fluidized bed. CN 106500091A adds W, Cr, Mo, and Nb high temperature resistant materials, and adds other metals to optimize the wear resistance of the material.
[0004] However, when metal materials are actually used in circulating fluidized bed boilers, the high internal temperature affects the molecular activity of the materials, so that the particles can still cause damage to the inner wall. Once scratches are generated inside the boiler, it will cause pressure imbalance in the area, further increasing the damage to the scratched area, and further weaken the thermal conductivity of the area, seriously affecting the service life of the circulating fluidized bed boiler. Summary of the invention
[0005] Technical issues solved: In view of the deficiencies in the prior art, the present invention provides a high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler, which has the advantages of not affecting the heat dissipation of the circulating fluidized bed boiler while further enhancing its internal wear resistance, and not affecting the heat dissipation even if wear occurs, thereby solving the problems of the above-mentioned technology.
[0006] Technical solution: To achieve the above object, the present invention provides the following technical solution: a high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler, wherein the material is prepared by mixing a high thermal conductivity component and a wear-resistant component, wherein the high thermal conductivity component comprises the following raw materials in the following mass ratio: Aluminum alloy 3-7%; Silicon nitride 2-3%; Silicon aluminum nitride 10-15%; Silicon nitride 10-15%; Reaction sintered silicon carbide 5-8%; Compacted silicon carbide 2-10%; Silicate binder 3-5%; Enhancer 3-7%; Modifier 2-7%; The wear-resistant component comprises the following raw materials in mass ratio: Magnesium-based ceramic composites 20-30%; Aluminum-based ceramic composites 20-25%; Tungsten carbide coating 1-2%; Titanium carbide coating 1-2%.
[0007] Preferably, the reinforcing agent is a fiber-reinforced material, and the fiber-reinforced material is prepared by mixing one or more of carbon fiber, ceramic fiber, silicate fiber and alumina fiber.
[0008] Preferably, the modifier is a mixture of one or more of silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride, and the minimum amount of the multiple mixtures is three of silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride.
[0009] Preferably, the high thermal conductivity component includes raw materials in the following mass ratios: aluminum alloy 6%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 11%; reaction sintered silicon carbide 5%; dense silicon carbide 6%; silicate binder 5%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes raw materials in the following mass ratios: magnesium-based ceramic composite material 24%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
[0010] Preferably, aluminum alloy 3%; silicon nitride 2%; silicon aluminum nitride 15%; silicon nitride 10%; reaction sintered silicon carbide 8%; dense silicon carbide 7%; silicate binder 4%; reinforcing agent 5%; modifier 4%; the wear-resistant component includes the following raw materials in the following mass ratio: magnesium-based ceramic composite material 20%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
[0011] Preferably, aluminum alloy 3%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 15%; reaction sintered silicon carbide 6%; dense silicon carbide 2%; silicate binder 4%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes the following raw materials in the following mass ratio: magnesium-based ceramic composite material 23%; aluminum-based ceramic composite material 22%; tungsten carbide coating 2%; titanium carbide coating 2%.
[0012] Preferably, the material preparation steps are: Step 1, combining the high thermal conductivity component mixture and the wear-resistant component mixture; Step 2: cold pressing or hot pressing the mixture into a mold, the cold pressing pressure is about 20-30 MPa, and the hot pressing temperature is controlled at 1000°C-1200°C; Step 3: Place the molding material in a high temperature furnace for sintering at a temperature of 1600°C-2000°C for 2-5 hours; Step 4: After sintering, slowly cool the material, clean and treat its surface to remove oil, dust and oxides; Step 5: Coating of tungsten carbide coating: spray, dip or brush the tungsten carbide coating evenly on the surface of the substrate, with the coating thickness controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake at 60-80°C; Coating of titanium carbide coating: after the tungsten carbide coating is completely dry, apply the titanium carbide coating, with the coating thickness also controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake; Step 6: Sintering: The coated material is sintered at a temperature of 800°C-1200°C for 1-3 hours. After sintering, the material is slowly cooled.
[0013] Preferably, the cold pressing pressure expression in step 2 is:
[0014] The expression of hot pressing temperature is: .
[0015] Preferably, the sintering temperature in step 3 is expressed as:
[0016] The sintering time expression is: .
[0017] Preferably, the sintering temperature in step 6 is expressed as:
[0018] The sintering time expression is: .
[0019] Compared with the prior art, the present invention provides a high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler, which has the following beneficial effects: 1. The present invention enhances the physical and chemical properties of the material by sintering the material within a temperature range of 800°C-1200°C, while not being too high to cause significant degradation of the material performance, ensuring that the thermal conductivity of the material is maintained at an appropriate level, and slowly cooling after sintering is completed to avoid rapid shrinkage or deformation of the material, thereby maintaining the stability of its structure. Ceramic materials such as silicon nitride (Si3N4) or silicon carbide (SiC) have high hardness and excellent wear resistance. The ceramic material is combined with a metal matrix and sintered to obtain a composite material with both high thermal conductivity and excellent wear resistance. The metal matrix is mixed with hard ceramic particles, and the composite material is manufactured through a sintering process, while taking into account wear resistance and thermal conductivity. A sintering aid is used to improve the density of the material and further enhance its wear resistance. By controlling the sintering temperature within an appropriate range, good density and uniformity of the material are ensured. Applying a wear-resistant coating on the surface of the material can further enhance the wear resistance and protect the material matrix from direct wear, thereby achieving the beneficial effect of not affecting the heat dissipation of the circulating fluidized bed boiler while further enhancing its internal wear resistance.
[0020] 2. The present invention uses aluminum and its alloys to have a high thermal conductivity of 200 W / m·K. Even if the surface is worn, its good thermal conductivity can maintain the heat dissipation performance of the boiler. Copper and its alloys have a higher thermal conductivity of 400 W / m·K. The high thermal conductivity of copper alloys can ensure that the heat dissipation performance is still relatively stable even under wear conditions. Silicon carbide ceramics have a high thermal conductivity of 120 W / m·K and an extremely high hardness of 9 Mohs. When used in composite materials, the wear resistance of the material is effectively improved while maintaining good thermal conductivity. A wear-resistant coating is applied to form a hard protective layer on the surface of the material, which reduces the impact of wear on the base material, maintains the thermal conductivity of the material, and improves its performance in a high wear environment, achieving the beneficial effect of not affecting heat dissipation even if wear occurs. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the preparation method of the circulating fluidized bed boiler of the present invention; DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] See also Figure 1 , a high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler, the material is prepared by mixing a high thermal conductivity component and a wear-resistant component, the high thermal conductivity component includes the following raw materials in mass ratio: Aluminum alloy 3-7%; Silicon nitride 2-3%; Silicon aluminum nitride 10-15%; Silicon nitride 10-15%; Reaction sintered silicon carbide 5-8%; Compacted silicon carbide 2-10%; Silicate binder 3-5%; Enhancer 3-7%; Modifier 2-7%; The wear-resistant component comprises the following raw materials in mass ratio: Magnesium-based ceramic composites 20-30%; Aluminum-based ceramic composites 20-25%; Tungsten carbide coating 1-2%; Titanium carbide coating 1-2%.
[0024] Aluminum-based materials: Aluminum and its alloys (aluminum-silicon alloys) have high thermal conductivity and can effectively conduct heat. Even if the surface of the material is worn, the heat dissipation effect can still be maintained at a high level due to its good thermal conductivity inside.
[0025] Copper-based materials: Copper and its alloys (copper-nickel alloys) also have high thermal conductivity, which can ensure efficient heat dissipation of the boiler system. The heat dissipation performance of copper-based materials is usually relatively stable, and even in the case of wear, the decrease in thermal conductivity is small.
[0026] Chromium alloy: The addition of chromium to the alloy can significantly improve the hardness and wear resistance of the material. High chromium alloys (chromium-nickel alloys) are often used in wear-resistant materials because chromium can form hard chromide and improve the wear resistance of the material.
[0027] Tungsten alloy: Tungsten and its alloys have extremely high hardness and wear resistance. Adding tungsten can significantly improve the wear resistance of the material, making it perform well in high-wear environments.
[0028] Ceramic materials: Ceramic materials such as silicon nitride (Si3N4) or silicon carbide (SiC) have high hardness and excellent wear resistance. By combining these ceramic materials with a metal matrix and sintering them, a composite material with high thermal conductivity and excellent wear resistance can be obtained.
[0029] Composite materials: A metal matrix (iron-based alloy) is mixed with hard ceramic particles (tungsten carbide particles) and a composite material is manufactured through a sintering process, which can achieve both wear resistance and thermal conductivity.
[0030] Sintering aids: The use of sintering aids (molybdenum or tungsten) can improve the density of the material and further enhance its wear resistance. Sintering aids can promote the densification of the material, reduce porosity, and thus improve wear resistance.
[0031] Sintering temperature control: By controlling the sintering temperature within an appropriate range (800℃-1200℃), good density and uniformity of the material are ensured, which helps maintain its thermal conductivity and improves its wear resistance.
[0032] Wear-resistant coating: Applying a wear-resistant coating (titanium nitride coating) on the surface of the material can further enhance the wear resistance and protect the material substrate from direct wear. The wear-resistant coating can effectively maintain the thermal conductivity of the material while increasing its service life in a high wear environment.
[0033] Preferably, the reinforcing agent is a fiber-reinforced material, and the fiber-reinforced material is prepared by mixing one or more of carbon fiber, ceramic fiber, silicate fiber and alumina fiber.
[0034] Preferably, the modifier is a mixture of one or more of silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride, and the minimum amount of the multiple mixtures is three of silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride.
[0035] Preferably, the high thermal conductivity component includes raw materials in the following mass ratios: aluminum alloy 6%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 11%; reaction sintered silicon carbide 5%; dense silicon carbide 6%; silicate binder 5%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes raw materials in the following mass ratios: magnesium-based ceramic composite material 24%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
[0036] Preferably, aluminum alloy 3%; silicon nitride 2%; silicon aluminum nitride 15%; silicon nitride 10%; reaction sintered silicon carbide 8%; dense silicon carbide 7%; silicate binder 4%; reinforcing agent 5%; modifier 4%; the wear-resistant component includes the following raw materials in the following mass ratio: magnesium-based ceramic composite material 20%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
[0037] Preferably, aluminum alloy 3%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 15%; reaction sintered silicon carbide 6%; dense silicon carbide 2%; silicate binder 4%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes the following raw materials in the following mass ratio: magnesium-based ceramic composite material 23%; aluminum-based ceramic composite material 22%; tungsten carbide coating 2%; titanium carbide coating 2%.
[0038] Preferably, the material preparation steps are: Step 1, combining the high thermal conductivity component mixture and the wear-resistant component mixture; Step 2: cold pressing or hot pressing the mixture into a mold, the cold pressing pressure is about 20-30 MPa, and the hot pressing temperature is controlled at 1000°C-1200°C; Step 3: Place the molding material in a high temperature furnace for sintering at a temperature of 1600°C-2000°C for 2-5 hours; Step 4: After sintering, slowly cool the material, clean and treat its surface to remove oil, dust and oxides; Step 5: Coating of tungsten carbide coating: spray, dip or brush the tungsten carbide coating evenly on the surface of the substrate, with the coating thickness controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake at 60-80°C; Coating of titanium carbide coating: after the tungsten carbide coating is completely dry, apply the titanium carbide coating, with the coating thickness also controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake; Step 6: Sintering: The coated material is sintered at a temperature of 800°C-1200°C for 1-3 hours. After sintering, the material is slowly cooled.
[0039] Preferably, the cold pressing pressure expression in step 2 is:
[0040] The hot pressing temperature expression is: .
[0041] Preferably, the sintering temperature in step 3 is expressed as:
[0042] The sintering time expression is: .
[0043] Preferably, the sintering temperature in step 6 is expressed as:
[0044] The sintering time expression is: .
[0045] Aluminum alloy: Aluminum and its alloys (aluminum silicon alloy) have high thermal conductivity (about 200 W / m·K). Even if the surface is worn, its good thermal conductivity can maintain the heat dissipation performance of the boiler.
[0046] Copper alloy: Copper and its alloys (copper-nickel alloy) have higher thermal conductivity (about 400 W / m·K). The high thermal conductivity of copper alloy ensures that the heat dissipation performance remains relatively stable even under wear.
[0047] High chromium alloy: Adding a high proportion of chromium (12% to 30%) can significantly improve the wear resistance of the material. Chromium can form a hard alloy phase (chromide) with other metal elements (nickel, molybdenum), improving the surface hardness and wear resistance of the material.
[0048] Tungsten alloy: Tungsten has extremely high hardness and wear resistance. Tungsten alloy (tungsten-molybdenum alloy) is often used in high wear-resistant environments. Its hardness (about 8-9 HRC) can effectively resist wear and extend the service life of the material.
[0049] Silicon carbide (SiC): Silicon carbide ceramics have high thermal conductivity (about 120 W / m·K) and extremely high hardness (about 9Mohs). When used in composite materials, they can effectively improve the wear resistance of the material while maintaining good thermal conductivity.
[0050] Silicon nitride (Si3N4): Silicon nitride ceramics have excellent thermal conductivity (about 30 W / m·K) and high wear resistance (hardness of 8-9 Mohs). During the sintering process, they can form a strong composite material with enhanced wear resistance and good heat dissipation when combined with a metal matrix.
[0051] Sintering aids: Adding sintering aids (molybdenum or tungsten) can improve the material's density and reduce porosity, thereby increasing the material's wear resistance and thermal conductivity. The dense material structure prevents a significant drop in thermal conductivity during wear.
[0052] High temperature sintering: Under controlled high temperature sintering, the particles in the material can be more tightly combined, improving the density and mechanical strength of the material, so that it can maintain good thermal conductivity even under wear conditions.
[0053] Wear-resistant coating: The application of wear-resistant coating (titanium nitride coating) can form a hard protective layer on the surface of the material, reducing the impact of wear on the base material. The coating can maintain the thermal conductivity of the material while improving its performance in high wear environments.
[0054] Surface hardening treatment: Surface hardening treatment (nitriding treatment) can improve the hardness and wear resistance of the material surface, protect the internal structure of the material from wear, and thus maintain the heat dissipation performance.
[0055] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler, characterized in that: The material is prepared by mixing a high thermal conductivity component and a wear-resistant component, wherein the high thermal conductivity component includes raw materials in the following mass ratios: Aluminum alloy 3-7%; Silicon nitride 2-3%; Silicon aluminum nitride 10-15%; Silicon nitride 10-15%; Reaction sintered silicon carbide 5-8%; Compacted silicon carbide 2-10%; Silicate binder 3-5%; Enhancer 3-7%; Modifier 2-7%; The wear-resistant component comprises the following raw materials in mass ratio: Magnesium-based ceramic composites 20-30%; Aluminum-based ceramic composites 20-25%; Tungsten carbide coating 1-2%; Titanium carbide coating 1-2%.
2. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 1, characterized in that: The reinforcing agent is a fiber-reinforced material, and the fiber-reinforced material is prepared by mixing one or more of carbon fiber, ceramic fiber, silicate fiber and alumina fiber.
3. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 2, characterized in that: The modifier is a mixture of one or more of silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride, and the minimum amount of the multiple mixed agents is three of the silicate, magnesium powder, calcium fluoride, graphene and aluminum nitride.
4. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 3, characterized in that: The high thermal conductivity component includes the following raw materials in mass ratio: aluminum alloy 6%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 11%; reaction sintered silicon carbide 5%; dense silicon carbide 6%; silicate binder 5%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes the following raw materials in mass ratio: magnesium-based ceramic composite material 24%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
5. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 1, characterized in that: Aluminum alloy 3%; silicon nitride 2%; silicon aluminum nitride 15%; silicon nitride 10%; reaction sintered silicon carbide 8%; dense silicon carbide 7%; silicate binder 4%; reinforcing agent 5%; modifier 4%; the wear-resistant component includes the following raw materials in mass ratio: magnesium-based ceramic composite material 20%; aluminum-based ceramic composite material 20%; tungsten carbide coating 1%; titanium carbide coating 1%.
6. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 1, characterized in that: Aluminum alloy 3%; silicon nitride 3%; silicon aluminum nitride 10%; silicon nitride 15%; reaction sintered silicon carbide 6%; dense silicon carbide 2%; silicate binder 4%; reinforcing agent 3%; modifier 5%; the wear-resistant component includes the following raw materials in the following mass ratio: magnesium-based ceramic composite material 23%; aluminum-based ceramic composite material 22%; tungsten carbide coating 2%; titanium carbide coating 2%.
7. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 1, characterized in that: The material preparation steps are: Step 1, combining the high thermal conductivity component mixture and the wear-resistant component mixture; Step 2: cold pressing or hot pressing the mixture into a mold, the cold pressing pressure is about 20-30 MPa, and the hot pressing temperature is controlled at 1000°C-1200°C; Step 3: Place the molding material in a high temperature furnace for sintering at a temperature of 1600°C-2000°C for 2-5 hours; Step 4: After sintering, slowly cool the material, clean and treat its surface to remove oil, dust and oxides; Step 5: Coating of tungsten carbide coating: spray, dip or brush the tungsten carbide coating evenly on the surface of the substrate, with the coating thickness controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake at 60-80°C; Coating of titanium carbide coating: after the tungsten carbide coating is completely dry, apply the titanium carbide coating, with the coating thickness also controlled at 0.1-0.5 mm, and allow the coating to dry naturally or bake; Step 6: Sintering: The coated material is sintered at a temperature of 800°C-1200°C for 1-3 hours. After sintering, the material is slowly cooled.
8. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 7, characterized in that: The cold pressing pressure expression in step 2 is: The hot pressing temperature expression is: 。 9. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 8, characterized in that: The sintering temperature expression in step 3 is: The sintering time expression is: 。 10. The high thermal conductivity and wear-resistant material for a circulating fluidized bed boiler according to claim 9, characterized in that: The sintering temperature expression in step 6 is: The sintering time expression is: 。
Citation Information
Patent Citations
High-temperature-resistant and abrasion-resistant material for circulating fluidized bed boiler
CN106500091A
Nano-carbon-reinforced wear-resistant composite material
CN105483420A
Titanium carbide-tungsten carbide alloy coating and preparation method thereof
CN108950344A
Coating composite material, preparation method of coating composite material, coating, crystallizer copper plate and surface treatment method of crystallizer copper plate
CN114940837A
High rate steel surface hard alloy coating preparing process using powder metallurgic method
CN1570207A